High Postural Sway Is an Independent Risk Factor for Osteoporotic Fractures but Not for Mortality in Elderly Women. (27th February 2019) - Qazi, Sarang Latif; Sirola, Joonas; Kröger, Heikki; Honkanen, Risto; Isanejad, Masoud; Airaksinen, Olavi; Rikkonen, Toni
ABSTRACT: The aim of this prospective cohort study was to investigate the independent effect of postural sway on overall fracture and osteoporotic fracture risk after controlling for other established fracture risk factors. As a secondary outcome, mortality was also investigated. The study sample is a stratified random sample of 1568 women born between 1932 and 1941, residing in Kuopio province, eastern Finland. Fracture data were obtained through study questionnaires and verified through hospital records. Mortality data were verified through the National Registry. Using static posturography, postural sway was recorded for 1568 women at the fifth year of follow‐up in 1994 through 1997. Mediolateral (ML), anteroposterior (AP), and total sway parameters were used for analysis. Mean follow‐up time for any fractures, osteoporotic fractures, and mortality was 10.6, 11.4, and 17.5 years, respectively. After adjustment, subjects in the highest quartile of ML sway (HR, 2.0; 95% CI, 1.5 to 2.8) and total sway (HR, 1.6; 95% CI, 1.2 to 2.2) had a higher risk for any fracture. Osteoporotic fracture risk was also higher in the fourth quartile of ML sway (HR, 1.9; 95% CI, 1.1 to 3.0) and total sway (HR, 1.7; 95% CI, 1.0 to 2.8). The models were adjusted for fracture risk assessment tool risk factors and leg‐extension strength. Further, women having both lowest bone density and highest postural sway were at 4.9 (95% CI, 2.6 to 9.5) times higher risk of overall fracture and 11.8 (95% CI, 2.7 to 51.3) times higher risk for osteoporotic fracture in comparison with subjects having highest bone density and lowest postural sway. The association between postural sway and mortality was not significant after adjustment. In conclusion, high postural sway is an independent risk factor for any fractures as well as for osteoporotic fractures. A combination of low bone density and high postural sway poses even higher fracture risk than either factor alone. Postural sway does not predict mortality independently. © 2019 American Society for Bone and Mineral Research.